Predicting individual responses to lithium with oxidative stress markers in drug-free bipolar disorder. (26th November 2019) - Lv, Qinyu; Guo, Yanhong; Zhu, Minghuan; Geng, Ruijie; Cheng, Xiaoyan; Bao, Chenxi; Wang, Yingyi; Huang, Xinxin; Zhang, Chen; Hao, Yong; Li, Zezhi; Yi, Zhenghui
Abstract: Objectives: This is the first study to investigate the oxidative stress (OxS) levels in drug-free bipolar disorder (BD) patients and their association with lithium response. Methods: A total of 61 drug-free BD patients and 49 controls were included. Patients treated with lithium were followed-up for 6 weeks. The levels of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT) and malondialdehyde (MDA) were measured at baseline and at the end of the sixth week. Results: Compared to controls, the SOD levels were lower, whereas the MDA were higher in the BD-depression (BD-D) group (both P < 0.001). GSH-Px levels were higher in both the BD-D and the BD-mania (BD-M) group (both P < 0.001). Both GSH-Px and MDA levels in the BD ( P = 0.009, P < 0.001) and the BD-D subgroup ( P = 0.006, P = 0.001) decreased significantly after the 6-week treatment with lithium. Interestingly, both GSH-Px and MDA levels decreased in responders ( P = 0.03, P = 0.002) but not in the non-responders of BD-D (both p > 0.05). Moreover, the reduction in the MDA levels were associated with lithium response ( B = 1.47, Wald statistic = 5.94, P = 0.015, odds ratio = 4.35, 95% confidence interval 1.33-14.20). Conclusions: Our study demonstrates an imbalance of OxS in drug-free BD, especially BD-D. Lithium reduces the GSH-Px and MDA levels in BD patients. The reduction in MDA levels may predict individual responsiveness to lithium.